Measuring critical force in sport climbers: a validation study of the 4 min all-out test on finger flexors - Jiří, Baláš; Jan, Gajdošík; Tomáš, Javorský; Patrik, Berta; Andri, Feldmann (European journal of applied physiology, 2024)
PURPOSE: The critical force (CF) concept, differentiating steady and non-steady state conditions, extends the critical power paradigm for sport climbing. This study aimed to validate CF for finger flexors derived from the 4 min all-out test as a boundary for the highest sustainable work intensity in sport climbers. METHODS: Twelve participants underwent multiple laboratory visits. Initially, they performed the 4 min intermittent contraction all-out test for CF determination. Subsequent verification visits involved finger-flexor contractions at various intensities, including CF, CF -2 kg, CF -4 kg, and CF -6 kg, lasting for 720 s or until failure, while monitoring muscle-oxygen dynamics of forearm muscles. RESULTS: CF, determined from the mean force of last three contractions, was measured at 20.1 ± 5.7 kg, while the end-force at 16.8 ± 5.2 kg. In the verification trials, the mean time to failure at CF was 440 ± 140 s, with only one participant completing the 720 s task. When the load was continuously lowered (-2 kg, -4 kg, and -6 kg), a greater number of participants (38%, 69%, and 92%, respectively) successfully completed the 720 s task. Changes of muscle-oxygen dynamics showed a high variability and could not clearly distinguish between exhaustive and non-exhaustive trials. CONCLUSIONS: CF, based on the mean force of the last three contractions, failed to reliably predict the highest sustainable work rate. In contrast, determining CF as the end-force of the last three contractions exhibited a stronger link to sustainable work. Caution is advised in interpreting forearm muscle-oxygen dynamics, lacking sensitivity for nuanced metabolic responses during climbing-related tasks.
Keywords: svalová kontrakce; Humans; Muscle Contraction; Mountaineering; Oxygen Consumption; Fingers; Female; mladý dospělý; dospělí; lidé; Adult; kosterní svaly; ženské pohlaví; prsty ruky; Male; horolezectví; Muscle, Skeletal; spotřeba kyslíku; Young Adult; mužské pohlaví